Optimal graft choice in athletic patients with anterior cruciate ligament injuries: review and clinical insights - Sim, K.; Rahardja, R.; Zhu, M.; Young, S. W. (Open Access Journal of Sports Medicine, 2022)
Anterior cruciate ligament (ACL) rupture is a common sporting-related knee injury with a potentially detrimental impact on the athlete`s career, yet there is no formal consensus on the optimal graft choice for reconstructing the ruptured ACL in this specific population. Options for reconstruction include autograft, allograft, and artificial grafts. However, each has associated failure risk and donor site morbidity. Our operational definition of the athlete is a skeletally mature individual participating in high level activity with the expectation to return to pre-injury level of activity. The athlete has unique injury characteristics, post-operative expectations, and graft demands that differ to the general population. Long-term outcomes are of particular importance given on-going mechanical demands on the reconstructed knee. Therefore, the purpose of this review is to consolidate current literature on the various ACL reconstruction graft options, with a focus on the optimal graft for returning the athlete to activity with the lowest rate of re-injury.